The role of Guidance Counseling Teachers (BK) in Finding Positive Personality in Class VIII (Eight) Students at SMP Negeri 2 Rantau Utara - Lila Madani Monthana; Fauziah Nasution (Universitas Muhammadiyah Enrekang, 2023)
This research uses a qualitative approach. Researchers obtain the required data directly from respondents in the field. The technique used in collecting research data is through interviews. The results of this research will be presented in the form of words that do not use statistical techniques. This research was conducted determine the role of guidance and counseling teachers in develoving positive personalities in class VIII students at SMP Negeri 2 Rantau Utara. Based on the results of the interview, it can be be concluded thet although it is not yet perfect due to inadequate facilities, the role of the BK teachers at SMP Negeri 2 Rantau Utara in develoving positive personalities for class VIII students has been carried out well, namely by carrying out character development, making a fixed schedule and collaborating with the school principal, subject teachers. This can be proven by the reduction in class VIII students who violate school rules,